GIÁP XÁC KÝ SINH TRÊN GHẸ CHỮ THẬP Charybdis feriata Linnaeus, 1758 KHU VỰC VỊNH NHA TRANG - Lê, Thị Kiều Oanh; Võ, Thị Hà; Nguyễn, Phương Liên; Nguyễn, Thị Hải Thanh; Hoàng, Ngọc Lâm; Đặng, Thúy Bình; Trương, Thị Oanh; Trần, Quang Sáng (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
PARASITIC CRUSTACEAN ON THE CRUCIFIX CRAB Charybdis feriata Linnaeus, 1758 IN NHA TRANG BAYCharybdis feriata (Linnaeus, 1758) is wide distribution and high economic value species in many countries around the world. In Vietnam, Charybdis feriata is on the list of endangered species that need to be conserved. Parasites cause many effects on the growth and development of crabs, which may be one of the causes leading to the decline of host populations. This paper presents the species composition, parasitic sites and infection status of parasitic crustaceans on C. feriata in Nha Trang Bay. From 113 individuals of Charybdis feriata collected in June and July 2022, we have identified 6 species of parasitic crustaceans, of which 2 species have been recorded for the first time on this crab, including: Octolasmis neptuni, Semibalanus sp.. Each infested crab is infected with up to 5 species of parasites. Octolasmis angulata was the dominant species with the highest prevalence and median intensity of infection at 44.4% and 6.5 individuals/infected crabs, respectively. Comparison of infection status by sex and host size showed that Sacculina serenei infection rate was higher in female crabs than male crabs, while infection intensity in male crabs was higher than female crabs. The prevalence and intensity of infection with Octolasmis angulata species increased significantly with host size. There was no statistical difference between the different host groups of sex and size. The data on parasitic crustaceans on Charybdis feriata contribute to the basis for the recovery, sustainable development of this endangered species.